Nutritional and Therapeutic Effects of Banana on Blood Pressure and Liver Health - Hoque, Majedul; Uddin, Md. Mayen; Rafi, Iftear Kazim (Journal of Tropical Pharmacy and Chemistry, 2025)
Although the prevalence of hypertension and related conditions is rising, there is currently little usage of functional foods as a therapy. Nutrients and bioactive substances found in bananas can help to prevent and treat a number of degenerative diseases. This study is to ascertain the impact of banana (Musa acuminata) on teenage student’s liver function, cholesterol levels, and blood pressure. The 32 respondents that made up the complete population provided samples for this experimental study. Blood pressure, liver function, and lipid function were assessed both before and after consuming bananas. The data in this study were analyzed using a paired t test. The majority of responders were in the fourteen-year-old age group, with the number of 13(40.62%) and 17(53.12%) in the ninth grade, while fewer number were in the eighth grade, with 5(15.62%). The results of the study showed that students liver function did not show considerable outcome, but their blood pressure changed considerably before and after eating bananas over the allotted time period and their lipid function levels (triglycerides and total cholesterol) also differed considerably. In conclusion, eating bananas might help to prevent degenerative diseases by decreasing blood pressure and maintaining low lipid levels in young people. Keywords:          Blood pressure, Liver function, Lipid function, Potassium, Triglycerides